2022
DOI: 10.1007/s10453-022-09772-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fungal aerosols in a public library with natural ventilation

Abstract: Fungal aerosols deteriorate library collections and can impact human health, mainly via respiratory diseases. Their spread is influenced by factors such as temperature and relative humidity. This study aims to assess the concentration of fungal aerosols in the interior environment of the Popular Library of Gaira in the District of Santa Marta, Colombia, using a two-stage cascade impactor utilizing Sabouraud dextrose agar on Petri dishes for the collection of samples. The sampler was positioned at 1.5 m above g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 71 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…macrocarpum, Cl. tenuissimum, P. digitatum, P. implicatum, P. oxalicum, P. simplicissimum), were reported in Brazilian library environments by Leite Jr. et al 37,109 Likewise, some Aspergillus species isolated in the NARC environment (A. candidus, A. flavus, A. glaucus, A. niger, A. ochraceus, A. versicolor) were recently detected in a Colombian library, 114 and many of the species of these three genera have been reported by other authors in archive and library of other countries, 66,67,74,82,84 as well as in museums. 73 Among the rare species detected before the year 2000 is Cladosporium werneckii Horta, which was reported by Vaillant et al 115 It has been known that it was later classified as Hortaea werneckii (Horta) Nishim.…”
Section: Diversity Of Fungal Genera and Species Reported In The Repos...mentioning
confidence: 88%
See 1 more Smart Citation
“…macrocarpum, Cl. tenuissimum, P. digitatum, P. implicatum, P. oxalicum, P. simplicissimum), were reported in Brazilian library environments by Leite Jr. et al 37,109 Likewise, some Aspergillus species isolated in the NARC environment (A. candidus, A. flavus, A. glaucus, A. niger, A. ochraceus, A. versicolor) were recently detected in a Colombian library, 114 and many of the species of these three genera have been reported by other authors in archive and library of other countries, 66,67,74,82,84 as well as in museums. 73 Among the rare species detected before the year 2000 is Cladosporium werneckii Horta, which was reported by Vaillant et al 115 It has been known that it was later classified as Hortaea werneckii (Horta) Nishim.…”
Section: Diversity Of Fungal Genera and Species Reported In The Repos...mentioning
confidence: 88%
“…This result was expected since most of its repositories have natural cross ventilation and outdoor air is considered by many authors to be the largest source of fungal propagules in indoor environments. 74,114,130,151,152…”
Section: Diversity Of Genera and Species Detected On The Documents Su...mentioning
confidence: 99%
“…The study of primary biological aerosol particles increases their importance, especially those focused on identifying and quantifying fungal spores [1]. The increasing interest in the utility of fungi as aerobiological particles is usually linked to agriculture and public health, as their presence is linked to phytopathological and allergological diseases [2][3][4]. A review of the spectrum of airborne fungal spores in Europe identified 67 taxa, where Alternaria and Cladosporium were the most common taxa studied due to their spores reporting the highest concentrations in northern Europe [5].…”
Section: Introductionmentioning
confidence: 99%